2017
DOI: 10.5483/bmbrep.2017.50.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib-mediated activation of endoplasmic reticulum stress induces de novo ceramide biosynthesis and apoptosis in hepatoma HepG2 cells

Abstract: Ceramides are the major sphingolipid metabolites involved in cell survival and apoptosis. When HepG2 hepatoma cells were treated with celecoxib, the expression of the genes in de novo sphingolipid biosynthesis and sphingomyelinase pathway was upregulated and cellular ceramide was elevated. In addition, celecoxib induced endoplasmic reticulum (ER) stress in a time-dependent manner. SPTLC2, a subunit of serine palmitoyltransferase, was overexpressed by adenovirus. Adenoviral overexpression of SPTLC2 (AdSPTLC2) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…We found that CerS6 overexpression led to the elevation of C16 ceramide levels, and decreased both Akt/mTOR and ERK phosphorylation, which plays a critical role in the proliferation of breast cancer (2,33,34). In accordance with previous reports (24)(25)(26), which showed that several anticancer reagents such as doxorubicin, celecoxib and methotrexate increase C16-ceramide, increased C16-ceramide induced by CerS6 overexpression reduced breast cancer cell growth with concomitant inhibition of both the Akt/mTOR and ERK pathways. Because the Akt/mTOR pathway is highly dysregulated in breast cancer and it also mediates resistance to endocrine therapies, mTOR inhibition has received significant attention as a novel therapy against breast cancer (35).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that CerS6 overexpression led to the elevation of C16 ceramide levels, and decreased both Akt/mTOR and ERK phosphorylation, which plays a critical role in the proliferation of breast cancer (2,33,34). In accordance with previous reports (24)(25)(26), which showed that several anticancer reagents such as doxorubicin, celecoxib and methotrexate increase C16-ceramide, increased C16-ceramide induced by CerS6 overexpression reduced breast cancer cell growth with concomitant inhibition of both the Akt/mTOR and ERK pathways. Because the Akt/mTOR pathway is highly dysregulated in breast cancer and it also mediates resistance to endocrine therapies, mTOR inhibition has received significant attention as a novel therapy against breast cancer (35).…”
Section: Discussionsupporting
confidence: 91%
“…CerS2 overexpression has been found to be correlated with breast cancer cell invasion and chemosensitivity (22,23). In addition, several anticancer drugs such as doxorubicin, celecoxib and methotrexate increase C16-ceramide levels and reduce cell growth (24)(25)(26). However, the precise molecular mechanisms and downstream signaling pathways of ceramide depending on the acyl chain length and S1P have not yet been elucidated in breast cancer.…”
Section: C16-ceramide and Sphingosine 1-phosphate/s1pr2 Have Oppositementioning
confidence: 99%
See 1 more Smart Citation
“…The ceramides are key lipid constituents of mammalian cells. They regulate the structural properties of the lipid bilayer [1] along with its interaction with cellular proteins [2], and control many signalling processes, including cell survival [3], growth and proliferation [4], differentiation [5], senescence [6] and apoptosis [7,8]. Dysfunctions in ceramide-mediated signalling may contribute to the initiation and progression of a variety of age-dependent diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramide levels are markedly reduced in HCC tissues due to the increased expression of strategies that stimulate its degradation, and hence, raising ceramide levels specifically within the tumor may be a relevant therapeutic approach [104]. In this regard, the celecoxib-mediated activation of ER-stress has been shown to induce de novo ceramide biosynthesis, resulting in enhanced apoptosis in hepatoma HepG2 cells [105]. Targeting ACDase, an enzyme that hydrolyzes ceramide (Figure 1), with LCL521 or carmofur has been shown to be of potential relevance in cancer [106,107].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%